Antimicrobial stewardship in paediatric oncology: Impact on optimising gentamicin use in febrile neutropenia. Issue 2 (13th September 2017) - Hennig, Stefanie; Staatz, Christine E.; Natanek, Daniel; Bialkowski, Sabina; Consuelo Llanos Paez, Carolina; Lawson, Rachael; Clark, Julia
Abstract: Objectives: To evaluate the impact of an antimicrobial stewardship (AMS) intervention, involving introduction of new guidelines on the treatment of febrile neutropenia (FN), on improving the use of gentamicin in paediatric oncology patients. Design and intervention: Updated guidelines for gentamicin usage in paediatrics with FN were implemented at a tertiary children's teaching hospital, in Brisbane, Australia. Data on gentamicin usage before and after the guideline change were collected retrospectively from children with cancer admitted to hospital with FN between January 2012 and December 2013. Gentamicin use, duration of gentamicin therapy and therapeutic monitoring practice were compared against bacterial culture status for admissions before and after the guideline change to assess the impact on practice. Results: Data were collected from 227 children corresponding to 453 separate admissions, 195 preguideline and 257 post‐guideline change. Following guideline change, the proportion of admissions in which gentamicin was administered reduced from 79.0 to 20.9% ( P ‐value < 0.001) and administrations not associated with a cultured Gram‐negative organism dropped from 87.2 to 58.2% ( P ‐value < 0.001), indicating a change in practice according to the new guideline. Following guideline change, admissions in which gentamicin was used for >48 hr despite the absence of a confirmed Gram‐negative infection decreased from 85.6 to 46.9% ( P ‐value < 0.001). Conclusions: Guideline changes driven through an AMS initiative involving paediatric oncology patients significantly improved targeted‐ and nontargeted‐antimicrobial use potentially reducing the risk of emergence of resistance against gentamicin in this cohort.